Effective and Simple NaOH-Modification Method to Remove Methyl Violet Dye via Ipomoea aquatica Roots. (13th October 2021) - Lu, Yie Chen; Kooh, Muhammad Raziq Rahimi; Lim, Linda Biaw Leng; Priyantha, Namal
Abstract : In this study, a simple chemical modification was applied to a sustainable and abundantly available resource, kangkong root (KR), to remove methyl violet 2B (MV) dye. The chemically modified adsorbent (NaOH-KR) was obtained using NaOH solution treatment. Batch adsorption experiments were carried out to investigate the effects of pH, ionic strength, contact time, adsorbent dosage, and initial dye concentration. A regeneration experiment was also carried out to assess the potential of reusability. The adsorption process was modelled using various kinetics and isotherm models, whereby the best-fitting models were evaluated by using the coefficient of determination (R 2 ) and error functions. The Sips (R 2 = 0.9714, χ 2  =0.16) and pseudo-second-order (R 2 = 0.9996, χ 2 = 0.007 ) models were identified to best represent the adsorption process. The Sips model predicted a maximum adsorption capacity at 551.5 mg g -1 for NaOH-KR, which is 55% improvement in performance when compared to nonmodified KR. Lastly, the regeneration experiment showed that NaOH-KR was able to maintain reasonable dye removal even after five consecutive cycles of regenerating and reusing.